Answer: 2, 1, 3, 4, 7, 11
======================================================
Work Shown:
f(1) = 2 is the first term
f(2) = 1 is the second term
Plug in n = 3. We add the first two terms to get the third term
f(n) = f(n-1)+f(n-2)
f(3) = f(3-1)+f(3-2)
f(3) = f(2)+f(1)
f(3) = 1+2
f(3) = 3
Now plug in n = 4 to get the fourth term
f(n) = f(n-1)+f(n-2)
f(4) = f(4-1)+f(4-2)
f(4) = f(3)+f(2) <<-- adding 3rd and 2nd term to get the 4th term
f(4) = 3+1
f(4) = 4
Repeat for n = 5.
f(n) = f(n-1)+f(n-2)
f(5) = f(5-1)+f(5-2)
f(5) = f(4)+f(3) <<-- adding 4th and 3rd term to get the 5th term
f(5) = 4+3
f(5) = 7
and the same for n = 6
f(n) = f(n-1)+f(n-2)
f(6) = f(6-1)+f(6-2)
f(6) = f(5)+f(4) <<-- adding 5th and 4th term to get the 6th term
f(6) = 7+4
f(6) = 11